The IMF in a World of Private Capital Markets - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2005)
The IMF attempts to catalyze and stabilize private capital flows to emerging markets by providing public monitoring and emergency finance. In analyzing its role we contrast cases where banks and bondholders do the lending. Banks have a natural advantage in monitoring and creditor coordination, while bonds have superior risk sharing characteristics. Consistent with this assumption, banks reduce spreads as they obtain more information through repeat transactions with borrowers. By comparison, repeat borrowing has little influence in bond markets, where publicly available information dominates. But spreads on bonds are lower when they are issued in conjunction with IMF-supported programs, as if the existence of a program conveyed positive information to bondholders. The influence of IMF monitoring in bond markets is especially pronounced for countries vulnerable to liquidity crises.